Relayed nuclear Overhauser enhancement sensitivity to membrane Cho phospholipids. Issue 4 (3rd April 2020) - Zu, Zhongliang; Lin, Eugene C.; Louie, Elizabeth A.; Xu, Junzhong; Li, Hua; Xie, Jingping; Lankford, Christopher L.; Chekmenev, Eduard Y.; Swanson, Scott D.; Does, Mark D.; Gore, John C.; Gochberg, Daniel F.
Abstract : Purpose: Phospholipids are key constituents of cell membranes and serve vital functions in the regulation of cellular processes; thus, a method for in vivo detection and characterization could be valuable for detecting changes in cell membranes that are consequences of either normal or pathological processes. Here, we describe a new method to map the distribution of partially restricted phospholipids in tissues. Methods: The phospholipids were measured by signal changes caused by relayed nuclear Overhauser enhancement‐mediated CEST between the phospholipid Cho headgroup methyl protons and water at around −1.6 ppm from the water resonance. The biophysical basis of this effect was examined by controlled manipulation of head group, chain length, temperature, degree of saturation, and presence of cholesterol. Additional experiments were performed on animal tumor models to evaluate potential applications of this novel signal while correcting for confounding contributions. Results: Negative relayed nuclear Overhauser dips in Z‐spectra were measured from reconstituted Cho phospholipids with cholesterol but not for other Cho‐containing metabolites or proteins. Significant contrast was found between tumor and contralateral normal tissue signals in animals when comparing both the measured saturation transfer signal and a more specific imaging metric. Conclusion: We demonstrated specific relayed nuclear Overhauser effects in partially restricted phospholipid phantoms and similar effects in solid brain tumors after correcting for confounding signal contributions, suggesting possible translational applications of this novel molecular imaging method, which we name restricted phospholipid transfer .